2021
DOI: 10.1002/smll.202006752
|View full text |Cite
|
Sign up to set email alerts
|

High Thermal Effusivity Nanocarbon Materials for Resonant Thermal Energy Harvesting

Abstract: Carbon nanomaterials have extraordinary thermal properties, such as high conductivity and stability. Nanocarbon combined with phase change materials (PCMs) can yield exceptionally high thermal effusivity composites optimal for thermal energy harvesting. The progress in synthesis and processing of high effusivity materials, and their application in resonant energy harvesting from temperature variations is reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…Generally, thermally conductive nanofillers, such as CNTs, graphene, expanded graphite (EG), and metal nanoparticles, are used to improve the thermal conductivity of PCMs. , Benefiting from the advantages of these materials, the compatible incorporation of thermally conductive nanofillers in GAs can yield high-performance thermally conductive frameworks. Liang et al reported shape-stabilized composite PCMs encapsulated with hybrid graphene aerogels (HGAs) consisting of GO and graphene.…”
Section: Carbon Aerogel-based Pcmsmentioning
confidence: 99%
“…Generally, thermally conductive nanofillers, such as CNTs, graphene, expanded graphite (EG), and metal nanoparticles, are used to improve the thermal conductivity of PCMs. , Benefiting from the advantages of these materials, the compatible incorporation of thermally conductive nanofillers in GAs can yield high-performance thermally conductive frameworks. Liang et al reported shape-stabilized composite PCMs encapsulated with hybrid graphene aerogels (HGAs) consisting of GO and graphene.…”
Section: Carbon Aerogel-based Pcmsmentioning
confidence: 99%
“…In contrast, extra additives result in disadvantages, such as a decrease in enthalpy, poor stability in long-term utilization, and increased cost. [34,35] More importantly, nanomaterials are prone to aggregation or sedimentation and cause deterioration of the heat transfer pathway during the long-term energy charging and discharging process. [36] The reason for the low thermal conduction efficiency of nanomaterials enhanced PCM composite resulting from the uneven dispersing of nanomaterials can be divided into two: the poor dispersing ability of nanomaterials in PCMs owing to unsatisfactory compatibility and density difference, and the aggregation of nanomaterials during long-term use.…”
Section: Nanomaterials Enhanced Thermal Conductivity Analysismentioning
confidence: 99%
“…Carbon nanostructures have found a wide variety of applications over the years thanks to their electronic and thermal conductivity, low density, and high mechanical strength, as well as the ability to undergo chemical functionalization to further tune their properties as needed for the intended use [39]. They are being studied especially for energy [40] and catalysis [41][42][43], including electro-catalysis [44,45] and nanozymes [46], as well as for the development of advanced electronic applications [47], including supercapacitors [48,49] and batteries [50], wearable electronics [51], electro-catalytic water-splitting [52], electromagnetic interference (EMI) shielding materials [53], molecular magnets [54], thermal-energy harvesting [55], photo-detectors [56], and electrochemical sensors [57]. In particular, in the area of sensing [58], recent developments have been made in the areas of nano-mass and nano-force sensors [59], gas sensors [60], biosensors [61], temperature sensors [62], and the growing field of touch or motion-driven sensors, or "haptics" [63].…”
Section: Carbon Nanostructures Properties and Usesmentioning
confidence: 99%